Hubungan Pengetahuan Perawat Terhadap Penerapan Dokumentasi Proses Keperawatan Berbasis SDKI, SLKI Dan SIKI DI RSUD Indramayu - Winani Winani; Bachtiar Efendi; Nurohmat Nurohmat (Yayasan Jompa Research and Development, 2022)
Nursing documentation is an obligation that must be carried out by nurses. Nursing documentation consists of formulating nursing diagnoses, making outcomes, and preparing nursing interventions. The purpose of the study: is to determine the relationship between nurses' knowledge of the application of nursing process documentation based on Indonesian nursing diagnosis standards, Indonesian nursing outcomes standards, and Indonesian nursing intervention standards at the Indramayu Regional General Hospital. Methods: descriptive quantitative research. The sampling technique pays attention to the inclusion and exclusion criteria. Results: the significance value (2-tailed) was 0.000. Because the significance value (2-tailed) <0.05, it means that there is a significant relationship between the Nurse Knowledge variable and the Application of Nursing Process Documentation. Discussion: the correlation coefficient of 0.258 means that the strength of the correlation/relationship between nurses' knowledge and the Application of Nursing Process Documentation Based on Indonesian Nursing Diagnosis Standards, Indonesian Nursing Outcomes Standards, and Indonesian Nursing Intervention Standards at the Indramayu Regional General Hospital is a sufficient relationship and the direction of the relationship is positive. In Rank Spearman the criteria are if the value of Sig is less than Alpha (0.05) then H1 is accepted (H0 is Rejected). H1: there is a relationship between nurses' knowledge and the application of Nursing Process Documentation Based on Indonesian Nursing Diagnosis Standards, Indonesian Nursing Outcomes Standards, and Indonesian Nursing Intervention Standards at the Indramayu Regional General Hospital